In vitro slow-release urea contained in rice straw-based diets to increase efficiency of rumen microbial protein synthesis - Kardaya, Dede; Wiryawan, K.G; Parakkasi, A; Winugroho, H.M (Indonesian Journal of Animal and Veterinary Sciences, 2010)
Effect of slow-release urea on efficiency of rumen microbial protein synthesis (EMPS) was examined using an in vitro technique. The objective of this experiment was to reveal the in vitro slow-release urea characteristics of zinc-urea, zeolites-urea, and zeolites-zinc-urea in relation to EMPS observed in different incubation time. The experimental design employed was randomized block design with 4 x 3 factorial plus a control treatment, and conducted in two replications. Factors were various urea sources (urea, zinc-urea, zeolites-urea, and zeolites-zinc-urea) and molasses concentrations (0%, 6%, and 12%) in rice straw-based diets. The control treatment was the rice straw-based diets containing neither urea nor molasses. Diets consisting of 45% rice straw and 55% concentrates (DM basis) were formulated to have similar N and TDN levels. Responses of parameters measured were subjected to MANOVA using the GLM procedure of SPSS 16.00 and differences among mean values, if applicable, were examined using HSD-test. Orthogonal comparisons were used to determine the effects of the control treatment vs. various urea sources. Results indicated that treatment of UZ combined with 6% of molasses showed the highest microbial biomass production (2.71 mg/l) at 24 hours fermentation period with its peak production estimation (3.2 mg/l) reached at 33.5 hours of fermentation period. Moreover, UZ treatment resulted in the highest microbial protein synthesis (1,381.45 Â± 77.1 mg/l) at 24 hours fermentation period with its peak microbial protein synthesis estimation (1,756.04 mg/l) reached at 33.7 hours of fermentation period. The highest EMPS (25.98 Â± 1.21 mg/100 mg OMD) was achieved when ration contained 6% of molasses. Key words: Slow-Release Urea, Microbial Protein Synthesis, Microbial Biomass, In vitro